Family‐based treatment for adolescents with anorexia nervosa: A long‐term psychological follow‐up. (25th June 2022) - Springall, Gabriella; Caughey, Michelle; Zannino, Diana; Cheung, Michael; Burton, Claire; Kyprianou, Kypros; Yeo, Michele
Abstract : Aim: Family‐based treatment (FBT) has the greatest evidence base for the treatment of adolescents with anorexia nervosa (AN). However, little is known about the long‐term outcomes for patients who receive FBT. The current study aimed to investigate the long‐term psychological health of former patients who received FBT for AN during adolescence. Methods: Former patients diagnosed and treated for AN at the Royal Children's Hospital and Monash Children's Hospital ( N = 36) in Melbourne, Australia completed self‐report questionnaires to assess eating, exercising, mood and the impact of the coronavirus (COVID‐19) pandemic. Patient scores were compared to healthy controls ( N = 29) and normative data. Results: The eating and exercising behaviours of the patients who formerly had AN were comparable to controls. However, the former patients experience significantly greater levels of depression, anxiety, and stress than the controls ( P < 0.05). The COVID‐19 pandemic appeared to impact the former patients and controls to a similar extent across quantifiable criteria. Conclusions: This study extends previous research highlighting FBT as an effective intervention for adolescents with AN. Positive short‐ and long‐term patient outcomes can be achieved with this form of treatment.